Ultra-broadband low scattering metasurface utilizing mixed-elements based on phase cancellation. (22nd October 2019) - Yang, Jianing; Huang, Cheng; Song, Jiakun; Ji, Chen; Luo, Xiangang
Abstract: Recently, phase cancellation metasurface has caused much attention due to its great capability of realizing radar cross section (RCS) reduction. However, owing to the intrinsic resonance property of the meta-atom, it is still challenging to expand the RCS reduction bandwidth. Here, we present a novel strategy to design ultra-broadband low-scattering metasurface by using the mixed meta-atoms combined with the evolutionary algorithm. The mixed meta-atoms are composed of single-layer or double-layer reflected elements, and the six different unit configurations are adopted to generate various reflection phases over a wide band. The planar array theory combined with particle swarm optimization (PSO) algorithm is employed to obtain the optimal mixed meta-atoms and their arrangement. The proposed low-scattering metasurface can achieve more than 10 dB RCS reduction between 5 and 18 GHz with a fractional bandwidth of 113% under normal incidence for both polarizations. The experimental results agree well with the simulated ones, and its bandwidth of the 10 dB RCS reduction reaches about 105.3%. In addition, our metasurface is still demonstrated to have the wide-angle stability for low-scattering property. The proposed design provides a feasible way to achieve ultra-broadband RCS reduction, which may find potential applications in electromagnetic fields.